Zmagania z niepewnością w biografiach członków rodzin emigrantów zarobkowych - Doiczman, Natasza (Kultura i Społeczeństwo, 2023)
The manner of functioning among family members who experience separation as a result of emigration shows that it is part of their biography, as a permanent element in the organisation of life. For the children of emigrants, the absence of a parent is an expression of the fact that the family’s functioning changed as a result of travelling abroad, depriving them of stability and predictability in family life. The remarks of emigrants’ family members remaining at home reflect the cyclical rhythm of everyday life, and indicate the day-to-day absence of the emigrant and their presence during holidays, which is a recipe for conflict. Emigration causes uncertainty. A fear of unexpected events, which occur without the presence of a parent who is simply unable to return on time, is characteristic of the children of emigrants. The feeling of insecurity and risk develops a kind of healing sense of temporariness, a sense that the state of separation will soon come to an end, which lowers the emotional tension of the family members remaining in Poland. The analysis presented in this article covers the findings of the author’s research, conducted using the biographical method on the everyday experiences of people whose reality was shaped by the hardships of migration separation. In many respects the research reveals that the beliefs of economic emigrants’ family members concerning the perception of separation is an experience that violates the imaginary image of a stable family.